The effect of price, discount, and customer rating on purchase decisions on the shopee marketplace - Mohamad Bagus Nuruddin; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Nurus Safa'atillah (Journal of Business Innovation and Accounting Research, 2025)
Shopee as the largest marketplace in Indonesia utilizes three elements, namely price, discount, and customer rating to increase sales transactions on the Shopee platform . This study aims to determine and analyze the influence of price, discount, and customer rating variables on purchasing decisions on the Shopee marketplace. The population in this study were students of the Faculty of Economics and Business, Lamongan Islamic University with a population of 859 students. This study uses a quantitative research method. Sampling using probability sampling techniques using random sampling methods and referring to the Slovin formula obtained results of 274 respondents. The results of this study indicate that partially and simultaneously the variables of price, discount , and customer rating have a positive and significant effect on purchasing decisions on the Shopee marketplace . Based on the results of the R square value, the three variables influence the purchasing decision variable by 71% so that the remaining 29% is influenced by other variables not examined in this study. This study contributes to adding to the literature that can be used as a reference for students to conduct further research, as well as being the main consideration for purchasing decisions online on the shopee marketplace . Further research is suggested to expand further research to other marketplaces and try to measure the long-term influence on purchasing decisions on the shopee marketplace.